Report on George Berkeley's Legacies at Trinity - Walsh, Patrick; O'Neill, Ciaran (My University, 2023)
This Working Paper details the memorialisation of Bishop George Berkeley (1685-1753) at Trinity College Dublin. It begins by first explaining who George Berkeley was, before moving on to discuss how he has been memorialised by successive generations in TCD, including but not limited to the Berkeley Library. The next section then provides detailed historical evidence on Bishop George Berkeley’s slave-owning activities and his ideological support for the slave system and settler colonialism. Section 4 then moves on to address the public submissions made to the Trinity Legacy Review Working Group (TLRWG) in January 2023 in response to the first working paper published by the TLRWG. The final section draws on international best practice to show how peer universities have dealt with/are dealing with similar issues in the contemporary context.
PUBLISHED
Keywords: Inclusive Society; Making Ireland; Public History